The Pelican history of the world - Roberts, J. M. (Penguin Books, 1980)
This book major is presented about Before history-Beginning; The first civilizations; The classical maditerranean; The age of diverging traditions; The making of the European age; The great acceleration; The end of European' World; The Post-European age,...